Tranformasi Ekonomi Berbasis Digital - Mutiarazora, Mita (Journal of Economics and Regional Science, 2021)
The purpose of this study was to determine the direction of the development of the industrial revolution. The method used is qualitative. We selected an exploratory case study design suitable for this study. To ensure the novelty of the data model for content analysis selected documents, articles, and scientific works. then the selection according to the research method. The discussion in this journal examines the process of the development of the Industrial Revolution and digital information technology which has undergone very rapid changes and developments in the world so as to be able to cause changes or transformations from the world community which has begun to switch and utilize it in various personal and social activities